Metal grid conductive silver paste and preparation method thereof

By using a specific proportion of silver powder, mixed resin and curing agent in the metal grid conductive silver paste, and through a stirring and airflow dispersion process, the problem of poor filling effect of silver paste in the prior art in ultra-fine grooves is solved, efficient conductive and filling performance is achieved, and the mechanical strength and binding force of the product are improved.

CN119694627APending Publication Date: 2025-03-25NANTONG AISHENG NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935863.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively fill silver paste in the 3-micron ultra-fine groove, resulting in problems such as circuit breakers and short circuits, and it is difficult to balance the conductive performance and filling performance.

Method used

Using a combination of 70-85 parts by mass of silver powder, 3-10 parts by mass of mixed resin, 5-15 parts by mass of organic solvent, 0.1-1.0 parts by mass of dispersant, 0.5-1.5 parts by mass of aliphatic isocyanate curing agent and cationic curing agent, a metal grid conductive silver paste with a fineness of 3 μm or less was prepared by stirring dispersion and multiple airflow dispersions of a microjet ultra-high pressure homogenizer.

Benefits of technology

It achieves good filling and low resistance of silver paste in 3 micron ultra-fine grooves, has strong mechanical strength and good binding ability to the substrate, reduces the loss of raw materials at the back end of the process and improves product yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694627A_ABST
    Figure CN119694627A_ABST
Patent Text Reader

Abstract

The invention provides metal grid conductive silver paste and a preparation method thereof, and belongs to the technical field of conductive paste. The metal grid conductive silver paste comprises the following components in parts by mass: 70-85 parts of silver powder; 3-10 parts by mass of a mixed resin; 5-15 parts by mass of an organic solvent; 0.1 to 1.0 part by mass of a dispersant; 0.5 to 1.5 parts by mass of a curing agent; wherein the curing agent is an aliphatic isocyanate curing agent and a cationic curing agent. When the metal grid conductive silver paste disclosed by the invention is applied to a metal grid flexible transparent conductive film, the metal grid conductive silver paste can be effectively filled in a 3-micron superfine groove and is cured in a short time, the paste is low in resistance value and has good bonding capacity with a base material, the loss of raw materials at the rear end of a manufacturing process is reduced, and the product yield is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive pastes, and in particular relates to a metal grid conductive silver paste and a preparation method thereof. Background Art

[0002] As user needs continue to change, touch technology is also constantly innovating and improving. In the future, touch panels will develop in the direction of low price, large size, and foldability. However, traditional ITO films are expensive, non-bendable, and cannot meet the increasingly diverse needs of customers, so more touch technology routes have emerged. Among them, metal grid technology forms metal lines on PET film, and has the characteristics of stable and controllable electrical properties, low cost, and foldability, providing strong technical support for large size, low resistance, and narrow borders. Therefore, this technology covers the size of flexible touch screens from the commonly used panel size of smartphones to 86 inches. Currently, products that use metal grid transparent conductive films to replace ITO transparent conductive films have been applied to different scenarios.

[0003] Currently, there are a variety of technical processes for preparing metal grid transparent conductive films. The mainstream process is to reserve a groove with a width of ≤4μm on the PET film through etching, UV glue curing, etc., and then scrape the conductive silver paste into the groove and perform low-temperature curing to form a metal grid touch electrode and surrounding leads to obtain a metal grid capacitive touch screen. This method has simple process, low cost, good light transmittance, and makes the product have the advantages of high flexibility. It has gradually become an important direction for the development of flexible, large-size, and thin touch screens. In the above-mentioned metal grid process technology, silver paste is one of its core raw materials. In order to achieve the requirements of high transparency and high conductivity, the groove width design of the product's visible area needs to reach ≤3μ

[0004] m, the resistivity must reach <1.5*10 -5Ω·cm. More importantly, the silver paste filled in the groove must have excellent bonding and mechanical properties with the substrate after low-temperature curing. However, the currently commonly used low-temperature silver paste, part of which is micron-grade silver paste, cannot be effectively filled in the 3-micron ultra-fine groove, and the filling effect is poor, resulting in serious open circuits and short circuits. Although the other part of the silver paste uses nano-scale small-particle silver powder, its effective contact (conduction) area after curing is relatively small, and it is necessary to use a high silver content to prepare the silver paste, and it is also necessary to maintain good fluidity to facilitate the filling of the groove, so it is difficult to achieve a balance between strong conductive properties and good filling properties. At the same time, silver powder also needs to be compounded with multiple components such as resin, adhesion promoter, coupling agent, curing agent, etc., and the formula components are complex. It is difficult to simultaneously achieve the excellent filling property of the silver paste, the low resistance after low-temperature baking and curing, the strong mechanical strength of itself, and the strong bonding with the substrate. Summary of the invention

[0005] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provides a metal grid conductive silver paste and a preparation method thereof.

[0006] In one aspect of the present disclosure, a metal grid conductive silver paste is provided, comprising:

[0007] 70-85 parts by mass of silver powder;

[0008] 3-10 parts by mass of mixed resin;

[0009] 5-15 parts by mass of an organic solvent;

[0010] 0.1-1.0 parts by mass of a dispersant;

[0011] 0.5-1.5 parts by mass of a curing agent; wherein,

[0012] The curing agent is an aliphatic isocyanate curing agent and a cationic curing agent.

[0013] Optionally, the aliphatic isocyanate curing agent is 3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate.

[0014] Optionally, the cationic curing agent is a boron trichloride amine complex.

[0015] Optionally, the silver powder is spherical silver powder with a particle size of 100-3000nm, a D50 of 300-700nm, a D90 of 2-3um, and a specific surface area of ​​1.0-2.0m 2 / g.

[0016] Optionally, the mixed resin is one or more of polyurethane resin, saturated polyester resin, polymethyl methacrylate resin, epoxy resin, phenoxy resin and ethyl cellulose resin.

[0017] Optionally, the mixed resin is a mixture of bisphenol A epoxy resin, thermoplastic polyurethane resin, thermoplastic polyurethane resin and dimethyl succinate.

[0018] Optionally, the mixed resin includes 20-26 parts by mass of bisphenol A epoxy resin;

[0019] 2-6 parts by mass of thermoplastic polyurethane resin;

[0020] 20-26 parts by mass of dipropylene glycol methyl ether;

[0021] 45-50 parts by mass of dimethyl succinate.

[0022] Optionally, the organic solvent is one or more of dimethyl carbonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, diethylene glycol butyl ether acetate, isophorone and dipropylene glycol methyl ether.

[0023] Optionally, the dispersant is one or more of a phospholipid dispersant, a polyurea dispersant, an ionic dispersant, and a non-ionic dispersant.

[0024] Another aspect of the present disclosure provides a method for preparing the metal grid conductive silver paste described above, the method comprising:

[0025] Get mixed resin;

[0026] The mixed resin, dispersant, curing agent, organic solvent and silver powder are added into a stirring disperser respectively, and stirred evenly for 50-60 minutes at a temperature of 15-25° C. and a stirring rate of 200-400 r / min to obtain a mixed slurry;

[0027] The mixed slurry is transferred to a microfluidizer with ultra-high pressure, and the air pressure is set at 5500-6500 Pa to perform air flow dispersion multiple times to obtain a metal grid conductive silver paste with a fineness of less than 3 μm.

[0028] Optionally, obtaining the mixed resin includes:

[0029] Add bisphenol A epoxy resin, thermoplastic polyurethane resin, dipropylene glycol methyl ether and dimethyl succinate into a container, stir for 2-3 hours at 80-100° C. and 1100-1300 r / min to obtain a mixed resin.

[0030] The present disclosure proposes a metal grid conductive silver paste and a preparation method thereof. The metal grid conductive silver paste comprises: 70-85 parts by mass of silver powder; 3-10 parts by mass of mixed resin; 5-15 parts by mass of organic solvent; 0.1-1.0 parts by mass of dispersant; 0.5-1.5 parts by mass of curing agent; wherein the curing agent is an aliphatic isocyanate curing agent and a cationic curing agent. When the conductive silver paste of the present disclosure is used in the metal grid flexible transparent conductive film, it can be effectively filled in the 3-micron ultra-fine groove and cured in a short time, and has good filling properties and strong mechanical strength. The paste has low resistance and good bonding ability with the substrate, which reduces the loss of raw materials at the back end of the process and improves the product yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a flowchart of a method for preparing a metal grid conductive silver paste according to a specific embodiment of the present disclosure. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0033] In one aspect of the present disclosure, a metal grid conductive silver paste is provided, comprising: 70~

[0034] 85 parts by mass of silver powder; 3-10 parts by mass of mixed resin; 5-15 parts by mass of organic solvent; 0.1-1.0 parts by mass of dispersant; 0.5-1.5 parts by mass of curing agent; wherein the curing agent is an aliphatic isocyanate curing agent and a cationic curing agent.

[0035] In this embodiment, by matching the ball powder silver powder with a cationic curing agent and an aliphatic isocyanate curing agent, the conductivity of the slurry and the adhesion to the substrate can be improved at the same time. On the one hand, the cationic curing agent forms a coordination complex containing hydrogen protons with the hydroxyl group in the system, triggering the epoxy group to carry out cationic ring-opening polymerization to form a polyether cross-linked network structure, thereby promoting the curing of the slurry. On the other hand, the aliphatic isocyanate curing agent reacts with the active hydrogen in the system to form a urea bond and a urea acid bond, while not affecting the printing of the silver paste, further strengthening the cross-linking of the silver paste with the substrate, thereby inhibiting the shedding of the silver paste. At the same time, the compounding of the cationic curing agent and the aliphatic isocyanate can promote the unsealing of the aliphatic isocyanate without affecting the volatility of the resin, accelerate the curing rate, and improve the quality after curing. In addition, after the silver paste is filled in the micron-level ultra-fine groove and baked at low temperature, the silver paste itself can produce strong mechanical properties, and can also obtain strong electrical conductivity, without the need to compound other components such as adhesion promoters and coupling agents, simplifying the formula of the slurry.

[0036] In some preferred embodiments, the content of the aliphatic isocyanate curing agent is preferably 0.5-0.8 parts by mass, for example, 0.5 parts by mass, 0.6 parts by mass, 0.75 parts by mass, 0.8 parts by mass, etc., and more preferably 0.6-0.8 parts by mass. The aliphatic isocyanate curing agent may preferably be 3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate, which has the characteristics of low deblocking temperature and high reactivity, and the auxiliary cationic curing agent promotes the formation of a more uniform and stable organic network structure inside the slurry, which is reflected in the compactness and uniformity after curing. An appropriate amount of aliphatic curing agent can improve the adhesion of the slurry to the substrate, and can also react with the active hydrogen in the system to form urea bonds and uric acid bonds, while not affecting the printability of the silver paste, further strengthening the crosslinking of the silver paste and the substrate, thereby inhibiting the shedding of the silver paste.

[0037] In other preferred embodiments, the content of the cationic curing agent is preferably 0.5-0.8 parts by mass, for example, 0.5 parts by mass, 0.6 parts by mass, 0.75 parts by mass, 0.8 parts by mass, etc., and more preferably 0.6-0.8 parts by mass. The cationic curing agent may preferably be a boron trichloride amine complex, which forms a coordination complex containing hydrogen protons with the hydroxyl groups in the system, triggering the epoxy groups to undergo cationic ring-opening polymerization to form a polyether cross-linked network structure, thereby promoting the curing of the slurry, so that the system can have higher reactivity and better electrical properties at 120-140°C.

[0038] As a further preferred embodiment, the content of the aliphatic isocyanate curing agent is the same as that of the cationic curing agent. For example, when the content of the cationic curing agent is 0.75 parts by mass, the content of the aliphatic isocyanate curing agent is also preferably 0.75 parts by mass.

[0039] Furthermore, the content of the silver powder may preferably be 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, etc., and the silver powder has a particle size of 100-3000nm, a D50 of 300-700nm, a D90 of 2-3um, and a specific surface area of ​​1.0-2.0m 2 / g.

[0040] As a further preferred embodiment, the particle size of the silver powder is preferably between 200-2500 nm, D50 is preferably between 300 and 500 nm, D90 is preferably between 2 and 2.5 μm, and the specific surface area is preferably between 1.5 and 2.0 m 2 / g, with good dispersibility.

[0041] Furthermore, the content of the mixed resin is preferably 3 parts by mass, 5 parts by mass, 8 parts by mass, 10 parts by mass, etc., and the mixed resin may preferably be one or more of polyurethane resin, saturated polyester resin, polymethyl methacrylate resin, epoxy resin, phenoxy resin and ethyl cellulose resin.

[0042] As a further preferred embodiment, the mixed resin is preferably a mixture of bisphenol A epoxy resin, thermoplastic polyurethane resin, thermoplastic polyurethane resin and dimethyl succinate. More preferably, it is 20-26 parts by mass of bisphenol A epoxy resin, 2-6 parts by mass of thermoplastic polyurethane resin, 20-26 parts by mass of dipropylene glycol methyl ether, and 45-50 parts by mass of dimethyl succinate. The mixed resin has a moderate volatilization rate and is more likely to meet the requirements of rapid solidification of the slurry and no voids after solidification.

[0043] As a further preferred embodiment, the mixed resin is formed by the following method: bisphenol A epoxy resin (Mw molecular weight 51000), thermoplastic polyurethane resin, dipropylene glycol methyl ether, and dimethyl succinate are added to a container in sequence, and stirred at 90°C and 1200 r / min for 2 hours to obtain a mixed resin.

[0044] Furthermore, the content of the organic solvent may preferably be 5 parts by mass, 7 parts by mass, 10 parts by mass, 12 parts by mass, 15 parts by mass, etc., and the organic solvent may be one or more of dimethyl carbonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, diethylene glycol butyl ether acetate, isophorone and dipropylene glycol methyl ether.

[0045] Furthermore, the content of the dispersant may preferably be 0.1 parts by mass, 0.3 parts by mass, 0.5 parts by mass, 0.8 parts by mass, 1.0 parts by mass, etc., and the dispersant may be one or more of a phospholipid dispersant (e.g., BYK-106, BYK-111), a polyurea dispersant (e.g., BYK-410), an ionic dispersant (e.g., ZetaSperse 1600), and a non-ionic dispersant (e.g., ZetaSperse 3600).

[0046] like Figure 1 As shown, another aspect of the present disclosure provides a method S100 for preparing the metal grid conductive silver paste described above, which specifically includes the following steps S110 to S130:

[0047] S110, adding bisphenol A epoxy resin, thermoplastic polyurethane resin, dipropylene glycol methyl ether and dimethyl succinate into a container, stirring at 80-100° C. and 1100-1300 r / min for 1-3 hours to obtain a mixed resin.

[0048] In step S110, the content of bisphenol A epoxy resin is preferably 20-26 parts by mass, for example, 20 parts by mass, 22 parts by mass, 24 parts by mass, 26 parts by mass, etc., and its molecular weight Mw may be preferably 51,000.

[0049] In step S110 , the content of the thermoplastic polyurethane resin may preferably be 2-6 parts by mass, for example, 2 parts by mass, 4 parts by mass, 6 parts by mass, etc.

[0050] In step S110, the content of dipropylene glycol methyl ether may preferably be 20 parts by mass, 22 parts by mass, 24 parts by mass, 26 parts by mass, etc.

[0051] In step S110 , the content of dimethyl succinate may preferably be 45 parts by mass, 47 parts by mass, 50 parts by mass, or the like.

[0052] In step S110, the stirring temperature is preferably 80°C, 90°C, 100°C, etc., and more preferably 90°C. The stirring rate is preferably 1100 r / min, 1200 r / min, 1300 r / min, and more preferably 1200 r / min. The stirring time is preferably 2 h, 2.5 h, 3 h, etc., and more preferably 2 h.

[0053] S120, respectively adding the mixed resin, dispersant, curing agent, organic solvent and silver powder into a stirring disperser, stirring evenly for 50-60 minutes at a temperature of 15-25° C. and a stirring rate of 200-400 r / min to obtain a mixed slurry.

[0054] In step S120, the stirring temperature may preferably be 15°C, 20°C, 25°C, etc., and may further preferably be 20°C. The stirring rate may preferably be 200r / min, 300r / min, 400r / min, etc., and may further preferably be 300r / min. The stirring time may preferably be 50min, 55min, 60min, etc., and may further preferably be 60min.

[0055] S130, transferring the mixed slurry to a micro-jet ultra-high pressure homogenizer, setting the air pressure at 5500-6500 Pa, and performing multiple air flow dispersions to obtain a metal grid conductive silver paste with a fineness of less than 3 μm.

[0056] In step S130, the gas pressure may preferably be 5500Pa, 6000Pa, 6500Pa, etc. Moreover, the mixed slurry may be transferred to the microfluidizer for three or more air flow dispersions, each dispersion lasting 2-3min, which is helpful to further refine the particles and improve the uniformity and stability of the slurry.

[0057] The preparation method of the metal grid conductive silver paste proposed in the present invention is simple. The compound based on two curing agents can make the paste solidify in a short time. After baking and curing, the paste has good bonding ability with the substrate, reduced resistance and strong mechanical strength, and reduces the loss of raw materials in the back end of the process, thereby improving product yield.

[0058] The preparation method of the metal grid conductive silver paste will be further described below in conjunction with specific examples:

[0059] Example 1

[0060] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50=456nm, D90=2.28μm; 12 parts of mixed resin, 0.3 parts of phosphate dispersant BYK-111, 11.7 parts of dipropylene glycol methyl ether, 0.5 parts of cationic curing agent (boron trichloride amine complex), and 0.5 parts of aliphatic isocyanate curing agent (3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate).

[0061] The above-mentioned conductive silver paste preparation method comprises the following steps:

[0062] Step 1: 24 parts of bisphenol A epoxy resin (Mw molecular weight 51000), 5 parts of thermoplastic polyurethane resin, 24 parts of dipropylene glycol methyl ether, and 47 parts of dimethyl succinate are added to a container in sequence, and stirred at 90° C. and 1200 r / min for 2 hours to obtain a mixed resin;

[0063] Step 2: Add 12 parts of the mixed resin formed in step 1 and the above-mentioned component materials into a stirring disperser in sequence, and stir evenly for 60 minutes at a circulating water temperature of 20° C. and a stirring rate of 300 r / min to obtain a mixed slurry;

[0064] Step 3: Transfer the mixed slurry to a microfluidizer, set the air pressure at 6000 Pa, disperse it three times, each time for 2 minutes, to obtain a metal grid conductive slurry.

[0065] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130° C. for 10 min, and its line resistance was tested to be 8.7Ω / cm. The silver paste had good adhesion on the UV glue slot without falling off. The resistance change rate after DH500h was 5.0%, and the filling property was excellent.

[0066] Example 2

[0067] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50=456nm, D90=2.28μm; 12 parts of mixed resin, 0.3 parts of phosphate dispersant BYK-111, 11.2 parts of dipropylene glycol methyl ether, 0.75 parts of cationic curing agent (boron trichloride amine complex), and 0.75 parts of aliphatic isocyanate curing agent (3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate).

[0068] Based on the above components, the preparation method of the conductive silver paste is the same as that of Example 1.

[0069] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130°C for 10 minutes, and its line resistance was tested to be 8.2Ω / cm. The silver paste had good adhesion on the UV glue slot without falling off. The resistance change rate after DH500h was 4.8%, and the filling property was excellent, which was better than that of Example 1.

[0070] Comparative Example 1

[0071] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50=456nm, D90=2.28μm; 12 parts of mixed resin, 0.3 parts of phosphate dispersant BYK-111, 12.2 parts of dipropylene glycol methyl ether, and 0.5 parts of cationic curing agent (boron trichloride amine complex).

[0072] Based on the above components, the preparation method of the conductive silver paste is the same as that of Example 1.

[0073] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130° C. for 10 min, and its line resistance was tested to be 8.9Ω / cm. The adhesion of the silver paste on the UV glue slot was poor and it was easy to fall off. The resistance change rate after DH500h was 4.9%, and the filling property was good.

[0074] Comparative Example 2

[0075] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50=456nm, D90=2.28μm; mixed resin 12 parts, phosphate dispersant BYK-111 0.3 parts, dipropylene glycol methyl ether 12.2 parts, aliphatic isocyanate curing agent (3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate) 0.5 parts.

[0076] Based on the above components, the preparation method of the conductive silver paste is the same as that of Example 1.

[0077] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130° C. for 10 min, and its line resistance was tested to be 9.0 Ω / cm. The adhesion of the silver paste on the UV glue slot was poor and it was easy to fall off. The resistance change rate after DH500h was 4.9%, and the filling property was good.

[0078] Comparative Example 3

[0079] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50 = 456nm, D90 = 2.28μm; 12 parts of mixed resin, 0.3 parts of phosphate dispersant BYK-111, 11.7 parts of dipropylene glycol methyl ether, 0.5 parts of cationic curing agent (3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate) boron trichloride amine complex, 0.5 parts of adhesion promoter (3-glycidyloxypropyl trimethoxysilane). Based on the above components, the preparation method of conductive silver paste is the same as that of Example 1.

[0080] Based on the above components, the preparation method of the conductive silver paste is the same as that of Example 1.

[0081] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130° C. for 10 min, and its line resistance was tested to be 9.3Ω / cm. The silver paste slightly fell off on the UV glue slot. The resistance change rate after DH500h was 5.3%, and the filling property was good.

[0082] Comparative Example 4

[0083] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50 = 456nm, D90 = 2.28μm; 12 parts of mixed resin, 0.3 parts of phosphate dispersant BYK-111, 11.2 parts of dipropylene glycol methyl ether, 0.5 parts of cationic curing agent (boron trichloride amine complex), 1.0 parts of adhesion promoter (3-glycidyloxypropyltrimethoxysilane). Based on the above components, the preparation method of conductive silver paste is the same as that of Example 1.

[0084] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130° C. for 10 min, and its line resistance was tested to be 10.0 Ω / cm. The silver paste slightly fell off on the UV glue slot, and the resistance change rate after DH500h was 6.1%, and the filling property was excellent.

[0085] Comparative Example 5

[0086] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50=456nm, D90=2.28μm; mixed resin 12 parts, phosphate dispersant BYK-111 0.3 parts, dipropylene glycol methyl ether 11.7 parts, cationic curing agent (boron trichloride amine complex) 0.5 parts, titanate coupling agent (bis(triethanolamine) titanate diisopropyl ester) 0.5 parts.

[0087] Based on the above components, the preparation method of the conductive silver paste is the same as that of Example 1.

[0088] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130° C. for 10 min, and its line resistance was tested to be 10.5Ω / cm. The adhesion of the silver paste on the UV glue slot was average and it fell off. The resistance change rate after DH500h was 6.7%, and the filling property was excellent.

[0089] Comparative Example 6

[0090] As shown in Table 1, the conductive silver paste of this embodiment is composed of the following materials by mass fraction: 75 parts of spherical silver powder, with a particle size of 200-2500nm and a specific surface area of ​​1.75m 2 / g, D50=456nm, D90=2.28μm; mixed resin 12 parts, phosphate dispersant BYK-111 0.3 parts, dipropylene glycol methyl ether 11.7 parts, cationic curing agent (boron trichloride amine complex) 0.5 parts, titanate coupling agent (diisopropyl di(acetylacetonate) titanate) 0.5 parts.

[0091] Based on the above components, the preparation method of the conductive silver paste is the same as that of Example 1.

[0092] Further, as shown in Table 2, the conductive paste obtained in this embodiment was cured at 130°C for 10 minutes, and its line resistance was tested to be 10.3Ω / cm. The adhesion of the silver paste on the UV glue slot was average and it fell off. The resistance change rate after DH500h was 7.1%, and the filling property was excellent.

[0093] Table 1 Formulas of various embodiments and comparative examples

[0094]

[0095] Table 2 Curing process parameters and test results of various embodiments and comparative examples

[0096]

[0097] In summary, according to Comparative Examples 1-2, when a single cationic curing agent or aliphatic isocyanate curing agent is used, the silver paste has poor adhesion in ultrafine grooves, good filling properties, and is prone to falling off. When a cationic curing agent is used in combination with an aliphatic isocyanate curing agent, the adhesion of the paste to the substrate can be improved. On the one hand, the boron amine complex forms a coordination complex containing hydrogen protons with the hydroxyl groups in the system, initiating a cationic ring-opening polymerization reaction of the epoxy groups to form a polyether cross-linked network structure, thereby promoting the curing of the paste. On the other hand, 3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate reacts with the active hydrogen in the system to form urea bonds and uric acid bonds, which further strengthens the cross-linking of the silver paste with the substrate without affecting the printability of the silver paste, thereby inhibiting the shedding of the silver paste.

[0098] Furthermore, according to Comparative Examples 3-4, it is found that adding 0.5% of an appropriate amount of adhesion promoter can improve the bonding ability between the slurry and the substrate, but there will still be slight shedding. When the addition amount is increased to 1.0%, the adhesion shedding problem is further aggravated, and its electrical properties will also be significantly improved.

[0099] Furthermore, according to Comparative Examples 5-6, it can be seen that the combination of a cationic curing agent and a titanate coupling agent cannot improve the adhesion of the slurry to the substrate, and at the same time, will lead to a certain degree of increase in electrical properties.

[0100] In summary, the silver paste of this embodiment does not require multi-component compounding. Only by combining the two curing agents to work synergistically, a silver paste with good adhesion can be obtained under the premise of using 200-2500nm silver powder. After baking and curing, it has low resistance and strong mechanical strength, as well as strong bonding force with the substrate, which meets the needs of filling in ultra-fine UV glue tanks.

[0101] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A metal grid conductive silver paste, characterized in that: include: 70-85 parts by mass of silver powder; 3-10 parts by mass of mixed resin; 5-15 parts by mass of an organic solvent; 0.1-1.0 parts by mass of a dispersant; 0.5-1.5 parts by mass of a curing agent; wherein, The curing agent is an aliphatic isocyanate curing agent and a cationic curing agent.

2. The metal grid conductive silver paste according to claim 1, characterized in that: The aliphatic isocyanate curing agent is 3-isocyanate methylene-3,5,5-trimethylcyclohexyl isocyanate.

3. The metal grid conductive silver paste according to claim 1, characterized in that: The cationic curing agent is a boron trichloride amine complex.

4. The metal grid conductive silver paste according to claim 1, characterized in that: The silver powder is spherical silver powder with a particle size of 100-3000nm, a D50 of 300-700nm, a D90 of 2-3um, and a specific surface area of ​​1.0-2.0m 2 / g.

5. The metal grid conductive silver paste according to claim 1, characterized in that: The mixed resin is one or more of polyurethane resin, saturated polyester resin, polymethyl methacrylate resin, epoxy resin, phenoxy resin and ethyl cellulose resin.

6. The metal grid conductive silver paste according to claim 5, characterized in that: The mixed resin is a mixture of bisphenol A epoxy resin, thermoplastic polyurethane resin, thermoplastic polyurethane resin and dimethyl succinate.

7. The metal grid conductive silver paste according to claim 1, characterized in that: The organic solvent is one or more of dimethyl carbonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, diethylene glycol butyl ether acetate, isophorone and dipropylene glycol methyl ether.

8. The metal grid conductive silver paste according to claim 1, characterized in that: The dispersant is one or more of a phospholipid dispersant, a polyurea dispersant, an ionic dispersant, and a non-ionic dispersant.

9. A method for preparing the metal grid conductive silver paste according to any one of claims 1 to 8, characterized in that: The method comprises: Get mixed resin; The mixed resin, dispersant, curing agent, organic solvent and silver powder are added into a stirring disperser respectively, and stirred evenly for 50-60 minutes at a temperature of 15-25° C. and a stirring rate of 200-400 r / min to obtain a mixed slurry; The mixed slurry is transferred to a microfluidizer with ultra-high pressure, and the air pressure is set at 5500-6500 Pa to perform air flow dispersion multiple times to obtain a metal grid conductive silver paste with a fineness of less than 3 μm.

10. The method according to claim 9, characterized in that The step of obtaining the mixed resin comprises: Add bisphenol A epoxy resin, thermoplastic polyurethane resin, dipropylene glycol methyl ether and dimethyl succinate into a container, stir for 2-3 hours at 80-100° C. and 1100-1300 r / min to obtain a mixed resin.